Don't make me go back, Mommy : a child's book about satanic ritual abuse - Sanford, Doris (Multnomah Press, 1990)
Five-year-old Allison is one of a group of children who are abused and subjected to horrible rituals at a perverse day care center, but with therapy and her parents' love she begins the healing process.